Elastic Properties of the Single-Walled Carbon Nanotubes - O.B. Protsenko; V.V. Yemelyanenko (Журнал нано- та електронної фізики)
In this paper the elastic properties of two main types of single-walled carbon nanotubes (armchair and zigzag) were simulated by analytical molecular mechanics models. The aim of this work is investigation and comparison of Young’s modulus, shear modulus and Poisson’s ratio variations of different types of tubes as functions of diameter. We obtained a set of closed-form expressions for the size-dependent elastic properties of armchair (n, n) and zigzag (n, 0) tubes, which are basic for constructing mathematical models. Using those models elastic properties of single-walled nanotubes were evaluated. It was predicted that zigzag tube is more sensitive to chirality then armchair. Young’s and shear modules of both tubes were decreasing with diameter increasing. Poisson’s ratio was ranging from 0.16 to 0.29 and from 0.32 to 0.42 for an armchair and zigzag tubes respectively, but it was independent on chirality. It can be seen that predicted values of elastic characteristics for zigzag tube are larger then that for armchair tube, especially for smaller tubes. Results of this research can be used for design, analysis and evaluating of functioning and creating new materials based on carbon nanotubes.